LITERATUR REVIEW: MENINGKATKAN KUALITAS KEPEMIMPINAN KEPALA SEKOLAH MELALUI PENGAMBILAN KEPUTUSAN YANG TEPAT - Edmundus Bawor; Venni Nabila Farah Muthmainnah; Nabila Kusuma Wardani; Teguh Trianung; Supadi Supadi (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
This article discusses the importance of making the right decisions in improving the quality of school principal's leadership. School principals play a crucial role in carrying out their duties and responsibilities as school leaders. By making the right decisions, the school principal can improve the quality of their leadership and provide positive benefits for all parties in the school environment, including students, teachers, and staff. This article also discusses strategies and techniques that can be used by school principals in making the right decisions, such as collecting relevant data, conducting careful data analysis, considering alternative options, and involving staff and students in the decision-making process. By implementing these strategies and techniques, the school principal can improve the quality of their leadership and create a more harmonious, productive, and competitive school environment. Therefore, this article hopes that school principals can understand the importance of making the right decisions in improving the quality of their leadership and be able to implement suitable strategies and techniques to achieve this goal. This way, it is expected that a better and higher-quality school environment can be created for students, teachers, and staff.